A non-silver seed silver powder conductive paste and preparation method thereof
By combining Cu@PPy@Ag composite material with silicone modified acrylic resin, non-silver seed silver powder conductive paste was prepared, which solved the problem of insufficient conductivity and oxidation resistance of existing silver-clad copper conductive paste, significantly improving the photoelectric conversion efficiency of solar cells and reducing costs.
Patent Information
- Application Number
- CN202411535662.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-31
- Publication Date
- 2025-03-28
- Estimated Expiration
- 2044-10-31
AI Technical Summary
In the application of existing silver-clad copper conductive paste in solar cells, due to the density and hole problems of silver layer coating, the conductivity and oxidation resistance are insufficient, which affects the photoelectric conversion efficiency.
Cu@PPy@Ag composite material is used as non-silver seed silver powder, and a core-shell composite material is formed through the reaction of materials such as acrylic acid, pyrrole and silver nitrate, and combined with silicone modified acrylic resin to prepare conductive paste.
It significantly improves the conductivity and oxidation resistance of the conductive paste, enhances the photoelectric conversion efficiency of solar cells, and reduces costs and extends service life.
Smart Images

Figure SMS_1
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of solar cells, and in particular to a non-silver seed silver powder conductive paste and a preparation method thereof. Background Art
[0002] Solar cell conductive paste is a key material in the production of photovoltaic cells. It is used to form electrodes on the cells and directly affects the photoelectric conversion efficiency and reliability of solar cells. With the rapid development of the photovoltaic industry, conductive paste technology has made significant progress, and the formula of silver paste and aluminum paste has been continuously optimized to improve the performance of cells and reduce costs. At the same time, the industry is actively exploring alternative materials, such as copper paste and silver-coated copper paste, to reduce dependence on high-priced silver.
[0003] Silver-coated copper is currently widely used as a substitute for silver powder in the preparation of conductive paste. Although the cost of raw materials can be reduced by plating a layer of silver on the surface of the copper powder to form a core-shell structure of silver-coated copper powder, it has become an ideal substitute for silver powder. However, the physical defects of the silver layer coating density and coating holes of the silver-coated copper powder, as well as the poor oxidation resistance and poor conductivity of the silver-coated copper powder in the slurry, have a non-negligible impact on the preparation of downstream silver-coated copper conductive slurry and the photoelectric conversion efficiency of the conductive slurry used in solar cells. Therefore, it is necessary to improve the comprehensive performance of the slurry due to the problems of poor oxidation resistance and poor conductivity of the powder, so as to meet its application in solar cells. Summary of the invention
[0004] In order to solve the above technical problems, the present invention provides a non-silver seed silver powder conductive paste and a preparation method thereof.
[0005] The purpose of the present invention can be achieved through the following technical solutions:
[0006] A non-silver seed silver powder conductive paste comprises the following raw materials in parts by weight: 30-90 parts of non-silver seed silver powder, 0-60 parts of silver powder, 4-10 parts of modified resin, 2-5 parts of glass powder, and 2-4 parts of organic solvent;
[0007] The organic solvent is one or more of alcohol ester dodecanedioate, dimethyl adipate, ethylene glycol diacetate and ethylene glycol phenyl ether;
[0008] The modified resin is an organosilicon-modified acrylic resin, which is prepared by the following steps:
[0009] Under nitrogen conditions, acrylic acid, methyl acrylate, ethyl methacrylate and γ-methacryloxypropyltrimethoxysilane are added to butyl acetate, and the mixture is heated and stirred to 70°C, and then 2,2-azobisisobutyronitrile butyl acetate solution is slowly added dropwise, and the temperature is maintained to condense and reflux for 6-8 hours, and then rotary evaporated, and methanol is added and stirred for 5-10 minutes to obtain a silicone-modified acrylic resin;
[0010] Further, the usage ratio of acrylic acid, methyl acrylate, ethyl methacrylate, γ-methacryloxypropyltrimethoxysilane, butyl acetate, 2,2-azobisisobutyronitrile butyl acetate solution and methanol is 1-3 g: 8-15 g: 15-25 g: 6-10 g: 80-120 mL: 10 mL: 30 mL;
[0011] Furthermore, the 2,2-azobisisobutyronitrile butyl acetate solution is prepared by mixing and stirring 2,2-azobisisobutyronitrile and butyl acetate in a dosage ratio of 0.2-0.6 g:10 mL.
[0012] The non-silver seed silver powder is a Cu@PPy@Ag composite material with a core-shell structure, which is prepared with copper powder as the core layer, polypyrrole as the middle layer, and silver as the outermost layer;
[0013] Further, the Cu@PPy@Ag composite material is prepared by the following steps:
[0014] Step A1, dispersing acrylic acid in tetrahydrofuran, adding 1-hydroxybenzotriazole and N,N-dimethylpyridine in sequence, stirring at 0°C for 25-35 minutes, slowly adding dicyclohexylcarbodiimide, stirring vigorously at room temperature for 12-16 hours, concentrating under reduced pressure, adding ethyl acetate, filtering and collecting the filtrate, and distilling under reduced pressure to obtain an intermediate product;
[0015] Step A2, add pyrrole to a flask containing methanol, stir and mix evenly under nitrogen, then add the intermediate product while stirring, raise the temperature to 35°C, react for 3-5h, and then transfer to a vacuum rotary evaporator to remove methanol and excess acrylic acid to obtain a pyrrole derivative;
[0016] Step A3, ultrasonically dispersing the nano copper powder in N,N-dimethylformamide, adding pyrrole and pyrrole derivatives, and ultrasonically stirring for 10-30 minutes, transferring to an autoclave, and hydrothermally reacting at 160-180° C. for 6-8 hours, filtering, washing, and freeze-drying to obtain a Cu@PPy composite material (polypyrrole-coated copper powder composite material);
[0017] Step A4, the Cu@PPy composite material is stirred evenly in N,N-dimethylformamide, and the silver nitrate solution is slowly added under stirring to adjust the pH of the system to 10-11, and then 80wt% hydrazine hydrate is added, and the reaction is carried out at 40°C for 25-45min, and the product is filtered and washed to collect the product, and then transferred to ethanol to soak for 1.5-2.5h, and then filtered and dried to obtain a Cu@PPy@Ag composite material (silver-coated Cu@PPy composite material);
[0018] Further, in step A1, the usage ratio of acrylic acid, tetrahydrofuran, 1-hydroxybenzotriazole, N,N-dimethylpyridine, dicyclohexylcarbodiimide and ethyl acetate is 0.01-0.02 mol: 100 mL: 0.012-0.025 mol: 0.3-0.6 g: 0.011-0.022 mol: 20-40 mL;
[0019] Further, in step A2, the ratio of pyrrole, methanol and intermediate product is 0.01-0.02 mol: 50 mL: 0.013-0.025 mol;
[0020] Further, in step A3, the usage ratio of nano copper powder, N,N-dimethylformamide, pyrrole and pyrrole derivative is 1-3 g: 20 mL: 1-2 mL: 0.5-1.5 mL;
[0021] Further, in step A4, the usage ratio of the Cu@PPy composite material, N,N-dimethylformamide, silver nitrate solution and hydrazine hydrate is 3-10 g: 100 mL: 100 mL: 60-100 mL;
[0022] Furthermore, the silver nitrate solution in step A4 is prepared by mixing and stirring silver nitrate and N,N-dimethylformamide in a dosage ratio of 0.005-0.02 mol:100 mL.
[0023] A method for preparing a non-silver seed silver powder conductive paste comprises the following steps:
[0024] The raw materials are weighed by weight, and the non-silver seed silver powder, silver powder, modified resin, glass powder and organic solvent are uniformly stirred, and then ground to a slurry fineness of 5-10 μm to obtain a non-silver seed silver powder conductive slurry.
[0025] Beneficial effects of the present invention:
[0026] The conductive paste prepared by the present invention has excellent conductive properties and is applied to solar cells, significantly improving the photoelectric conversion efficiency of solar cells. Compared with the high cost caused by the use of a large amount of silver powder in traditional pastes, the paste has the advantages of low cost, good safety performance, and long service life.
[0027] Adding silicone-modified acrylic resin as an organic carrier to the conductive paste can effectively improve the high temperature resistance of the paste. This is because its presence can make the conductive paste more stable at high temperatures, making it less likely to deform or fail in high temperature environments. It also has the excellent chemical corrosion resistance of silicone, which enables the conductive paste to resist corrosion from various chemicals and extend its service life. At the same time, it also improves the electrical insulation of the conductive paste, ensuring the safety performance of solar cells in high-voltage environments.
[0028] The Cu@PPy@Ag composite material first utilizes the reaction between the carboxyl group in acrylic acid and the hydroxyl group in 1-hydroxybenzotriazole to generate an intermediate product containing a double bond structure; then utilizes the reaction between the double bond in the intermediate product and the secondary amine in pyrrole to generate a pyrrole derivative containing a benzotriazole structure; then uses pyrrole and pyrrole derivatives as monomers to synthesize a polypyrrole film on the surface of nano copper powder to obtain a Cu@PPy composite material; then uses silver nitrate to provide silver ions, and the silver ions are complexed on the surface of the Cu@PPy composite material, and the silver ions are reduced to silver under the action of a reducing agent to obtain a Cu@PPy@Ag composite material. Cu@PPy@Ag composite materials are used in the conductive paste of solar cells, which improves the conductive properties of the conductive paste, thereby significantly improving the photoelectric conversion efficiency of solar cells, and solving the shortcomings of the traditional conductive paste on the market, such as reduced conductivity caused by replacing silver powder with silver-coated copper due to cost reduction; the composite material adopts a double-layer coated core-shell structure, which is more uniformly coated, and improves the antioxidant and conductive properties of the composite material. This is because the pyrrole polymer coated with pyrrole and pyrrole derivatives as monomers has excellent conductivity, which further improves the conductive properties of the composite material. At the same time, the introduction of The benzotriazole structure can form covalent bonds and coordination bonds with copper atoms on the copper surface, thereby forming a protective film on the surface of the copper powder, effectively reducing the decrease in conductivity caused by copper oxidation, thereby enabling copper to maintain good conductivity; in addition, the polymer also contains active groups that can chelate silver ions in the solution to form a stable silver ion complex, so that the silver ions can be stably present on the surface of the Cu@PPy composite material, so as to facilitate the reduction treatment of the silver ions and achieve silver powder coating. The silver powder coated in this way has excellent stability and better coating properties, and can greatly reduce the amount of silver coating and reduce the slurry cost. DETAILED DESCRIPTION
[0029] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0030] Example 1
[0031] The silicone-modified acrylic resin is prepared by the following steps:
[0032] Under nitrogen conditions, acrylic acid, methyl acrylate, ethyl methacrylate and γ-methacryloxypropyltrimethoxysilane were added to butyl acetate, and the mixture was heated and stirred to 70°C, and then 2,2-azobisisobutyronitrile butyl acetate solution was slowly added dropwise, and the temperature was maintained to condense and reflux for 6 hours, and then rotary evaporated, and methanol was added and stirred for 5 minutes to obtain a silicone-modified acrylic resin;
[0033] Furthermore, the dosage ratio of acrylic acid, methyl acrylate, ethyl methacrylate, γ-methacryloyloxypropyltrimethoxysilane, butyl acetate, 2,2-azobisisobutyronitrile butyl acetate solution and methanol is 1g:8g:15g:6g:80mL:10mL:30mL, and 2,2-azobisisobutyronitrile butyl acetate solution is prepared by mixing and stirring 2,2-azobisisobutyronitrile and butyl acetate in a dosage ratio of 0.2g:10mL.
[0034] The Cu@PPy@Ag composite material was prepared by the following steps:
[0035] Step A1, dispersing acrylic acid in tetrahydrofuran, adding 1-hydroxybenzotriazole and N, N-lutidine in sequence, stirring at 0°C for 25 minutes, slowly adding dicyclohexylcarbodiimide, stirring vigorously at room temperature for 12 hours, concentrating under reduced pressure, adding ethyl acetate, filtering and collecting the filtrate, and distilling under reduced pressure to obtain an intermediate product, wherein the amount ratio of acrylic acid, tetrahydrofuran, 1-hydroxybenzotriazole, N, N-lutidine, dicyclohexylcarbodiimide and ethyl acetate is 0.01 mol: 100 mL: 0.012 mol: 0.3 g: 0.011 mol: 20 mL;
[0036] Step A2, add pyrrole to a flask containing methanol, stir and mix evenly under nitrogen, then add the intermediate product while stirring, and heat to 35°C, react for 3 hours, and then transfer to a vacuum rotary evaporator to remove methanol and excess acrylic acid to obtain a pyrrole derivative, wherein the amount ratio of pyrrole, methanol and intermediate product is 0.01 mol: 50 mL: 0.013 mol;
[0037] Step A3, ultrasonically dispersing the nano copper powder in N, N-dimethylformamide, adding pyrrole and pyrrole derivatives and ultrasonically stirring for 10 minutes, transferring to an autoclave, hydrothermally reacting at 160° C. for 6 hours, filtering, washing, and freeze-drying to obtain a Cu@PPy composite material, wherein the amount ratio of the nano copper powder, N, N-dimethylformamide, pyrrole and pyrrole derivatives is 1 g: 20 mL: 1 mL: 0.5 mL;
[0038] Step A4, the Cu@PPy composite material is stirred evenly in N, N-dimethylformamide, and the silver nitrate solution is slowly added under stirring conditions to adjust the pH of the system to 10, and then 80wt% hydrazine hydrate is added, and the reaction is carried out at 40°C for 25min, and the product is filtered and washed, and the product is collected, and then transferred to ethanol and soaked for 1.5h, and then filtered and dried to obtain the Cu@PPy@Ag composite material, wherein the amount ratio of the Cu@PPy composite material, N, N-dimethylformamide, the silver nitrate solution and the hydrazine hydrate is 3g:100mL:100mL:60mL, and the silver nitrate solution is prepared by mixing and stirring silver nitrate and N, N-dimethylformamide in an amount ratio of 0.005mol:100mL.
[0039] Example 2
[0040] The silicone-modified acrylic resin is prepared by the following steps:
[0041] Under nitrogen conditions, acrylic acid, methyl acrylate, ethyl methacrylate and γ-methacryloxypropyltrimethoxysilane were added to butyl acetate, and the mixture was heated and stirred to 70°C, and then 2,2-azobisisobutyronitrile butyl acetate solution was slowly added dropwise, and the temperature was maintained to condense and reflux for 7 hours, and then rotary evaporated, and methanol was added and stirred for 7 minutes to obtain a silicone-modified acrylic resin;
[0042] Furthermore, the dosage ratio of acrylic acid, methyl acrylate, ethyl methacrylate, γ-methacryloyloxypropyltrimethoxysilane, butyl acetate, 2,2-azobisisobutyronitrile butyl acetate solution and methanol is 2g:11g:20g:8g:100mL:10mL:30mL, and 2,2-azobisisobutyronitrile butyl acetate solution is prepared by mixing and stirring 2,2-azobisisobutyronitrile and butyl acetate in a dosage ratio of 0.4g:10mL.
[0043] The Cu@PPy@Ag composite material was prepared by the following steps:
[0044] Step A1, dispersing acrylic acid in tetrahydrofuran, adding 1-hydroxybenzotriazole and N,N-dimethylpyridine in sequence, stirring at 0°C for 30 minutes, slowly adding dicyclohexylcarbodiimide, stirring vigorously at room temperature for 14 hours, concentrating under reduced pressure, adding ethyl acetate, filtering and collecting the filtrate, and distilling under reduced pressure to obtain an intermediate product, wherein the amount ratio of acrylic acid, tetrahydrofuran, 1-hydroxybenzotriazole, N,N-dimethylpyridine, dicyclohexylcarbodiimide and ethyl acetate is 0.015 mol: 100 mL: 0.017 mol: 0.45 g: 0.016 mol: 30 mL;
[0045] Step A2, add pyrrole to a flask containing methanol, stir and mix evenly under nitrogen, then add the intermediate product while stirring, and heat to 35°C, react for 4 hours, and then transfer to a vacuum rotary evaporator to remove methanol and excess acrylic acid to obtain a pyrrole derivative, wherein the amount ratio of pyrrole, methanol and intermediate product is 0.015 mol:50 mL:0.018 mol;
[0046] Step A3, ultrasonically dispersing the nano copper powder in N, N-dimethylformamide, adding pyrrole and pyrrole derivatives and ultrasonically stirring for 20 minutes, transferring to an autoclave, hydrothermally reacting at 170° C. for 7 hours, filtering, washing, and freeze-drying to obtain a Cu@PPy composite material, wherein the amount ratio of the nano copper powder, N, N-dimethylformamide, pyrrole and pyrrole derivatives is 2g:20mL:1.5mL:1mL;
[0047] Step A4, the Cu@PPy composite material is stirred evenly in N, N-dimethylformamide, and the silver nitrate solution is slowly added under stirring conditions to adjust the pH of the system to 10.5, and then 80wt% hydrazine hydrate is added, and the reaction is carried out at 40°C for 35min, and the product is filtered and washed, and the product is collected, and then transferred to ethanol and soaked for 2h, and then filtered and dried to obtain a Cu@PPy@Ag composite material, wherein the amount ratio of the Cu@PPy composite material, N, N-dimethylformamide, the silver nitrate solution and the hydrazine hydrate is 6g:100mL:100mL:80mL, and the silver nitrate solution is prepared by mixing and stirring silver nitrate and N, N-dimethylformamide in an amount ratio of 0.01mol:100mL.
[0048] Example 3
[0049] The silicone-modified acrylic resin is prepared by the following steps:
[0050] Under nitrogen conditions, acrylic acid, methyl acrylate, ethyl methacrylate and γ-methacryloxypropyltrimethoxysilane were added to butyl acetate, and the mixture was heated and stirred to 70°C, and then 2,2-azobisisobutyronitrile butyl acetate solution was slowly added dropwise, and the temperature was maintained to condense and reflux for 8 hours, and then rotary evaporated, and methanol was added and stirred for 10 minutes to obtain a silicone-modified acrylic resin;
[0051] Furthermore, the dosage ratio of acrylic acid, methyl acrylate, ethyl methacrylate, γ-methacryloyloxypropyltrimethoxysilane, butyl acetate, 2,2-azobisisobutyronitrile butyl acetate solution and methanol is 3g:15g:25g:10g:120mL:10mL:30mL, and 2,2-azobisisobutyronitrile butyl acetate solution is prepared by mixing and stirring 2,2-azobisisobutyronitrile and butyl acetate in a dosage ratio of 0.6g:10mL.
[0052] The Cu@PPy@Ag composite material was prepared by the following steps:
[0053] Step A1, dispersing acrylic acid in tetrahydrofuran, adding 1-hydroxybenzotriazole and N,N-dimethylpyridine in sequence, stirring at 0°C for 35 minutes, slowly adding dicyclohexylcarbodiimide, stirring vigorously at room temperature for 16 hours, concentrating under reduced pressure, adding ethyl acetate, filtering and collecting the filtrate, and distilling under reduced pressure to obtain an intermediate product, wherein the amount ratio of acrylic acid, tetrahydrofuran, 1-hydroxybenzotriazole, N,N-dimethylpyridine, dicyclohexylcarbodiimide and ethyl acetate is 0.02 mol: 100 mL: 0.025 mol: 0.6 g: 0.022 mol: 40 mL;
[0054] Step A2, add pyrrole to a flask containing methanol, stir and mix evenly under nitrogen, then add the intermediate product while stirring, and heat to 35°C, react for 5 hours, and then transfer to a vacuum rotary evaporator to remove methanol and excess acrylic acid to obtain a pyrrole derivative, wherein the amount ratio of pyrrole, methanol and intermediate product is 0.02 mol:50 mL:0.025 mol;
[0055] Step A3, ultrasonically dispersing the nano copper powder in N, N-dimethylformamide, adding pyrrole and pyrrole derivatives and ultrasonically stirring for 30 minutes, transferring to an autoclave, hydrothermally reacting at 180° C. for 8 hours, filtering, washing, and freeze-drying to obtain a Cu@PPy composite material, wherein the amount ratio of the nano copper powder, N, N-dimethylformamide, pyrrole and pyrrole derivatives is 3g:20mL:2mL:1.5mL;
[0056] Step A4, the Cu@PPy composite material is stirred evenly in N, N-dimethylformamide, and the silver nitrate solution is slowly added under stirring conditions to adjust the pH of the system to 11, and then 80wt% hydrazine hydrate is added, and the reaction is carried out at 40°C for 45min, and the product is filtered and washed, and the product is collected, and then transferred to ethanol and soaked for 2.5h, and then filtered and dried to obtain a Cu@PPy@Ag composite material, wherein the amount ratio of the Cu@PPy composite material, N, N-dimethylformamide, the silver nitrate solution and the hydrazine hydrate is 10g: 100mL: 100mL: 100mL, and the silver nitrate solution is prepared by mixing and stirring silver nitrate and N, N-dimethylformamide in an amount ratio of 0.02mol: 100mL.
[0057] Example 4
[0058] A method for preparing a non-silver seed silver powder conductive paste comprises the following steps:
[0059] 30 parts of non-silver seed silver powder (Cu@PPy@Ag composite material prepared in Example 1), 60 parts of silver powder, 4 parts of modified resin (organosilicon-modified acrylic resin prepared in Example 1), 2 parts of glass powder, and 2 parts of dimethyl adipate;
[0060] The raw materials were weighed by weight, and the non-silver seed silver powder (Cu@PPy@Ag composite material prepared in Example 1), silver powder, modified resin (organosilicon-modified acrylic resin prepared in Example 1), glass powder and dimethyl adipate were uniformly stirred, and then ground to a slurry fineness of 10 μm to obtain a non-silver seed silver powder conductive slurry.
[0061] Example 5
[0062] A method for preparing a non-silver seed silver powder conductive paste comprises the following steps:
[0063] 50 parts of non-silver seed silver powder (Cu@PPy@Ag composite material prepared in Example 2), 40 parts of silver powder, 7 parts of modified resin (organosilicon-modified acrylic resin prepared in Example 2), 4 parts of glass powder, and 3 parts of dimethyl adipate;
[0064] The raw materials were weighed by weight, and the non-silver seed silver powder (Cu@PPy@Ag composite material prepared in Example 2), silver powder, modified resin (organosilicon-modified acrylic resin prepared in Example 2), glass powder and dimethyl adipate were uniformly stirred, and then ground to a slurry fineness of 7 μm to obtain a non-silver seed silver powder conductive slurry.
[0065] Example 6
[0066] A method for preparing a non-silver seed silver powder conductive paste comprises the following steps:
[0067] 90 parts of non-silver seed silver powder (Cu@PPy@Ag composite material prepared in Example 3), 5 parts of silver powder, 10 parts of modified resin (organosilicon-modified acrylic resin prepared in Example 3), 5 parts of glass powder, and 4 parts of dimethyl adipate;
[0068] The raw materials were weighed by weight, and the non-silver seed silver powder (Cu@PPy@Ag composite material prepared in Example 3), silver powder, modified resin (organosilicon-modified acrylic resin prepared in Example 3), glass powder and dimethyl adipate were uniformly stirred, and then ground to a slurry fineness of 5 μm to obtain a non-silver seed silver powder conductive slurry.
[0069] Comparative Example 1
[0070] This comparative example is a conductive paste, which differs from Example 5 in that commercially available silver-coated copper powder is used instead of the Cu@PPy@Ag composite material prepared in Example 2, and the rest are the same.
[0071] Comparative Example 2
[0072] This comparative example is a conductive paste, which is different from Example 5 in that acrylic resin is used instead of the organosilicon-modified acrylic resin prepared in Example 2, and the rest are the same.
[0073] After printing the conductive pastes prepared in Examples 4-6 and Comparative Examples 1-2, solar cells were prepared. The photoelectric conversion efficiency of the solar cells was tested and the conversion efficiency was tested using a German Berger tester PSS10-HE.
[0074] The test results are shown in Table 1:
[0075] Table 1
[0076]
[0077] It can be seen from the above table that after the conductive paste prepared by the present invention is used in a solar cell for photoelectric conversion efficiency testing, the conversion efficiency is in the range of 25.45%-25.63%, indicating that after the Cu@PPy@Ag composite material and the silicone-modified acrylic resin are introduced into the paste, the solar cell prepared by the paste has excellent conversion efficiency.
[0078] The above contents are merely examples and explanations of the concept of the present invention. The technicians in this technical field may make various modifications or additions to the specific embodiments described or replace them in a similar manner. As long as they do not deviate from the scope defined by the concept of the invention, they should all fall within the protection scope of the present invention.
Claims
1. A non-silver seed silver powder conductive paste, characterized in that: The method comprises the following raw materials in parts by weight: 30-90 parts of non-silver seed silver powder, 0-60 parts of silver powder, 4-10 parts of modified resin, 2-5 parts of glass powder, and 2-4 parts of organic solvent; The non-silver seed silver powder is a Cu@PPy@Ag composite material with a core-shell structure, which is prepared with copper powder as the core layer, polypyrrole as the middle layer, and silver as the outermost layer; The modified resin is an organosilicon-modified acrylic resin, which is prepared by the following steps: Under nitrogen conditions, acrylic acid, methyl acrylate, ethyl methacrylate and γ-methacryloxypropyltrimethoxysilane are added to butyl acetate, and the mixture is heated and stirred to 70°C. Then, 2,2-azobisisobutyronitrile butyl acetate solution is slowly added dropwise, and the temperature is maintained to condense and reflux for 6-8 hours. The mixture is rotary evaporated, and methanol is added and stirred for 5-10 minutes to obtain a silicone-modified acrylic resin.
2. The non-silver seed silver powder conductive paste according to claim 1, characterized in that: The dosage ratio of acrylic acid, methyl acrylate, ethyl methacrylate, γ-methacryloxypropyltrimethoxysilane, butyl acetate, 2,2-azobisisobutyronitrile butyl acetate solution and methanol in the silicone-modified acrylic resin is 1-3g:8-15g:15-25g:6-10g:80-120mL:10mL:30mL.
3. The non-silver seed silver powder conductive paste according to claim 2, characterized in that: The 2,2-azobisisobutyronitrile butyl acetate solution is prepared by mixing and stirring 2,2-azobisisobutyronitrile and butyl acetate in a dosage ratio of 0.2-0.6 g:10 mL.
4. The non-silver seed silver powder conductive paste according to claim 1, characterized in that: The organic solvent is one or more of alcohol ester dodecanedioate, dimethyl adipate, ethylene glycol diacetate and ethylene glycol phenyl ether.
5. The non-silver seed silver powder conductive paste according to claim 1, characterized in that: The Cu@PPy@Ag composite material is prepared by the following steps: Step A1, dispersing acrylic acid in tetrahydrofuran, adding 1-hydroxybenzotriazole and N,N-dimethylpyridine in sequence, stirring at 0°C for 25-35 minutes, slowly adding dicyclohexylcarbodiimide, stirring vigorously at room temperature for 12-16 hours, concentrating under reduced pressure, adding ethyl acetate, filtering and collecting the filtrate, and distilling under reduced pressure to obtain an intermediate product; Step A2, add pyrrole to a flask containing methanol, stir and mix evenly under nitrogen, then add the intermediate product while stirring, raise the temperature to 35°C, react for 3-5h, and then transfer to a vacuum rotary evaporator to remove methanol and excess acrylic acid to obtain a pyrrole derivative; Step A3, ultrasonically dispersing the nano copper powder in N, N-dimethylformamide, adding pyrrole and pyrrole derivatives and ultrasonically stirring for 10-30 minutes, transferring to an autoclave, hydrothermally reacting at 160-180°C for 6-8 hours, filtering, washing, and freeze-drying to obtain a Cu@PPy composite material; Step A4, stirring the Cu@PPy composite material in N, N-dimethylformamide, slowly adding a silver nitrate solution under stirring conditions, adjusting the pH of the system to 10-11, then adding 80wt% hydrazine hydrate, reacting at 40°C for 25-45 minutes, filtering, washing, collecting the product, and then transferring it to ethanol to soak for 1.5-2.5 hours, then filtering and drying to obtain a Cu@PPy@Ag composite material.
6. The non-silver seed silver powder conductive paste according to claim 5, characterized in that: In step A1, the usage ratio of acrylic acid, tetrahydrofuran, 1-hydroxybenzotriazole, N,N-dimethylpyridine, dicyclohexylcarbodiimide and ethyl acetate is 0.01-0.02 mol: 100 mL: 0.012-0.025 mol: 0.3-0.6 g: 0.011-0.022 mol: 20-40 mL.
7. The non-silver seed silver powder conductive paste according to claim 5, characterized in that: The usage ratio of pyrrole, methanol and intermediate product in step A2 is 0.01-0.02 mol:50 mL:0.013-0.025 mol.
8. The non-silver seed silver powder conductive paste according to claim 5, characterized in that: In step A3, the usage ratio of nano copper powder, N,N-dimethylformamide, pyrrole and pyrrole derivative is 1-3 g: 20 mL: 1-2 mL: 0.5-1.5 mL.
9. The non-silver seed silver powder conductive paste according to claim 5, characterized in that: In step A4, the amount ratio of the Cu@PPy composite material, N,N-dimethylformamide, silver nitrate solution and hydrazine hydrate is 3-10g:100mL:100mL:60-100mL, and the silver nitrate solution is prepared by mixing and stirring silver nitrate and N,N-dimethylformamide in an amount ratio of 0.005-0.02mol:100mL.
10. A method for preparing the non-silver seed silver powder conductive paste according to any one of claims 1 to 9, characterized in that: The following steps are involved: The raw materials are weighed by weight, and the non-silver seed silver powder, silver powder, modified resin, glass powder and organic solvent are uniformly stirred, and then ground to a slurry fineness of 5-10 μm to obtain a non-silver seed silver powder conductive slurry.
Citation Information
Patent Citations
One-step synthesis method of ternary composite conductive powder
CN109585053A
Superfine line printing conductive paste and preparation method and application thereof
CN114464344A